PERAN EKSTRAKURIKULER ROHIS DALAM PEMBENTUKKAN AKHLAK SISWA SMA NEGERI 1 TAYAN HILIR - Inka Yuliana; Dartim Dartim (Universitas Muhammadiyah Surakarta, 2022)
This research was carried out to know the role of Rohis extracurricular in shaping the morals of students at SMA Negeri 1 Tayan Hilir, and the things that support and hinder these activities. Data collection is based on real conditions in the field or field research and includes qualitative research with a phenomenological approach. The result of this research is that the implementation of Rohis in SMA Negeri 1 Tayan Hilir in its role in moral formation has been said to be quite good and effective. Where Rohis is a da'wah institution for the formation of students' morals with several activities such as reading and writing the Qur'an (BTA), Friday donations, fast boarding schools, comparative studies, and social services. The response of the students was also good, they were happy and enthusiastic about the religious activities held by Rohis. Supporting things such as the appreciation shown by the school and the students, a good environment for the development of student character, and adequate infrastructure. Inhibiting factors such as the lack of active students and the density of teaching and learning activities so that Rohis activities are not optimally carried out every week.